CRISIS IN THE REGENERATION OF LIVESTOCK WORKFORCE, ANALYSIS OF FACTORS AFFECTING YOUNG GENERATION'S INTEREST IN THE LIVESTOCK SECTOR - khaliq, taufik dunialam; Susanti S, Irma; Haloho, Ruth Dameria; Ermanda, Adli Putra; Pratiwi, Nita Adillah; Marsudi, Marsudi; Suriansyah, Suriansyah (Fakultas Peternakan, Universitas Padjadjaran, 2025)
The purpose of this research is to analyze the factors affecting the interest of the young generation in the livestock sector. The research was conducted in the province of West Sulawesi, using a sample of 230 people selected through purposive sampling. Instrument testing used the Pearson product-moment and Alpha Cronbach. Data analysis used multiple linear regression, with variables consisting of independent variables: social factors (X1), economic factors (X2), government role (X3), demographics (X4), information access (X5), and technology support (X6), with the dependent variable being interest in working in the livestock sector (Y). The results of this study indicate that simultaneously, all independent variables—social factors, economic factors, government support, demographics, information access, and technology support—affect the dependent variable, which is the interest of youth in working in the livestock sector. Partially, only government support does not influence interest, while the variable with the greatest impact is the economic factor. The strength of the relationship between the independent variable and the dependent variable can be seen in the correlation coefficient (R) with a value of 0.871, which means the correlation is very strong. The magnitude of the influence of the independent variable on the dependent variable is reflected in the coefficient of determination (R2) value of 0.761 or 76.1%, in other words, there are other variables influencing outside the model by 23.9%.